Furin inhibits HSCs activation and ameliorates liver fibrosis by regulating PTEN‐L/PINK1/parkin mediated mitophagy in mouse - Yan‐Wei Song; Yu‐Hua Zhu; Ming‐Ze Ma (FASEB BioAdvances)
Abstract Hepatic Stellate cells (HSCs) play an important role during liver fibrosis progression; more and more evidence indicates that mitophagy greatly regulates HSCs activation. HSCs mitophagy mainly depends on the classical PINK1/Parkin pathway, which can be strongly regulated by phosphatase PTEN‐long (PTEN‐L). PTEN‐L can be cleaved by Furin that leading to functional changes in the tumor regulation process. However, the impact of the interaction between Furin and PTEN‐L on HSCs mitophagy remains unclear. Therefore, this study aims to explore the role of Furin in HSCs activation and liver fibrosis and its potential mechanisms. Our results revealed that Furin expression was obviously up‐regulated during HSCs activation and mice liver fibrogenesis. We also found that the activation of primary HSCs can be inhibited by Furin treatment in vitro. Besides, functional studies showed that LX‐2 cell proliferation and migration were obviously inhibited by Furin treatment. Further studies showed that mitochondrial membrane potential (MMP) was significantly reduced by Furin treatment, and the knockdown of PTEN‐L expression caused similar effects. These results demonstrated the role of Furin in promoting HSCs mitophagy but leading to inhibition of HSCs persistent activation. Furthermore, we constructed a liver fibrosis mouse model by CCl4‐induced method and found that forced expression of Furin caused alleviation of liver fibrosis in CCl4‐induced mice. Our findings provide a new clue for understanding liver fibrogenesis and highlight the therapeutic potential of Furin for hepatic fibrosis.